Sero-Prevalence of Mycoplasma gallisepticum Infection of Chickens in Model Breeder Poultry Farms of Bangladesh - Sarkar, S.K.; Rahman, M.B.; Rahman, M.; Amin, K.M.R.; Khan, M.F.R.; Rahman, M.M. (International Journal of Poultry Science, 2004)
The sero-prevalence of Mycoplasma gallisepticum (MG) infection of chickens in selected Model Breeder Poultry Farms was determined during the period January to May, 2004. To conduct this study a total of 382 sera samples were collected. Rapid Serum Plate Agglutination (SPA) test was performed using commercial MG antigen (Nobilis® MG) to detect the presence of antibodies against MG. The over all sero-prevalence of MG infection was 58.90% in the study area. The highest prevalence (62.44 %) of MG infection was found in winter season followed by summer season (53.10%). The result further revealed that the infection was higher (59.94%) in female birds than in male birds (48.57%). It was also demonstrated that the infection was higher (62.80%) in Feni sadar than in Chhagoalnaiya thana (53.45%).